Discipline and indulgence : college football, media, and the American way of life during the Cold War - Montez de Oca, Jeffrey (Critical issues in sport and society., 2013)
This book demonstrates how American popular culture during the early Cold War (1947-1964), especially college football, addressed the nation's postwar affluence and consumerism and their effects on the population by integrating men into the economy of the Cold War as workers, warriors, and consumers. It assesses the period's institutional linkage of sport, higher education, media, and militarism and finds connections of contemporary sport media to the War on Terror.